THE EFFECTIVENESS OF THE ENDORPHIN, OXYTOCIN, AND SUGGESTIVE MASSAGE STIMULATION METHOD ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS: IMPLICATIONS FOR MIDWIFERY EDUCATION - Mahastra Aulya Kartika; Rifzul Maulina; Nila Widya Keswara (EDUCATIONE, 2025)
Breast milk is the optimal source of nutrition for infants, but exclusive breastfeeding rates in Indonesia and globally remain below target, largely due to maternal anxiety, insufficient milk production, and inadequate support systems. Innovative, integrative interventions that address both physiological and psychological barriers are urgently needed to support successful lactation outcomes. This study aimed to evaluate the effectiveness of the Stimulasi Pijat Endorphin, Oksitosin, dan Sugestif (SPEOS) method—an integrative technique combining oxytocin massage, endorphin massage, and positive suggestion—in increasing breast milk production among postpartum mothers at PMB Fatimah Bandungrejosari, Malang. A quasi-experimental posttest-only control group design was implemented, involving 36 postpartum mothers (days 1–40) who were divided equally into intervention and control groups. The intervention group received the SPEOS method (20-minute sessions for nine consecutive days), while the control group received only standard informational leaflets. Data on breast milk production were collected using validated observation sheets and baby scales, and analyzed using univariate and bivariate methods, including the Mann-Whitney test. The findings revealed that 66.7% of mothers in the SPEOS group achieved high breast milk production, compared to just 16.7% in the control group. Statistical analysis confirmed a significant difference between groups (p = 0.002). The SPEOS intervention demonstrated not only physiological benefits, through hormonal stimulation, but also psychological benefits, by improving maternal confidence and emotional well-being. The SPEOS method is an effective, holistic, and easily adopted intervention for enhancing breast milk production in postpartum mothers. Its integrative approach, targeting both hormonal and psychological pathways, makes it suitable for inclusion in maternal health education and practice. This research supports the integration of the SPEOS method into midwifery education and practice as a low-cost, evidence-based strategy to promote exclusive breastfeeding, maternal empowerment, and optimal infant health. The study provides a foundation for further research and broader implementation in diverse healthcare settings. Larger-scale and longer-term studies are recommended to confirm these findings, explore additional maternal and infant health outcomes, and refine SPEOS implementation protocols for various populations.